Investigation of hemodynamic changes in abdominal aortic aneurysms treated with fenestrated endovascular grafts - Sun, Zhonghua; Chaichana, Thanapong; Allen, Yvonne B.; Sangworasil, Manas; Tungjitkusolmun, Supan; Hartley, David E.; Lawrence-Brown, Michael M.D. (My University, 2009)
Fenestrated stent grafts are becoming widely used in clinical practice to treat patients with complicated aortic aneurysms, with short to mid-term satisfactory outcomes being achieved. However, long-term results are yet to be determined. One of the main concerns about the safety of fenestrated repair is the patency of fenestrated renal arteries and subsequent renal function. The purpose of this study is to investigate the hemodynamic changes in patients treated with fenestrated stent grafts using a two-way fluid-structure interaction. 4 patients undergoing fenestrated stent graft repair were selected for inclusion in our analysis. All of the fenestrated renal arteries remained patent after implantation of stent grafts with one patient developing post-procedural complication, endoleak. Our results showed that with insertion of fenestrated stents into the renal arteries with variable lengths, no significant changes of blood flow velocity were noticed based on the flow analysis. Our preliminary study indicates the safety of fenestrated stent grafts, however, further studies are required to verify the long-term outcome of this procedure.
Keywords: Aortic aneurysm; Blood flow; Fenestration; Stent graft